Transcranial color-coded sonography findings of patients with reversible cerebral vasoconstriction syndromes. (March 2019) - Terasawa, Yuka; Arai, Ayumi; Sakai, Kenichiro; Mitsumura, Hidetaka; Iguchi, Yasuyuki
Highlights: We report two cases of reversible cerebral vasoconstriction syndrome (RCVS). Transcranial color-coded ultrasonography showed bimodal PSV peak. Posterior circulation peak preceded anterior circulatioin peak. Abstract: Reversible cerebral vasoconstriction syndromes (RCVS) have been well recognized recently as one cause of cerebrovascular disease, but the time course of vessel vasoconstriction remains uncertain. We report herein 2 cases with RCVS in which we clarified temporal changes in vessel vasoconstriction in detail using transcranial color-coded sonography (TCCS). The first case involved a 27-year-old woman who developed intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH) after severe headache. TCCS showed peak systolic velocity (PSV) in the left middle cerebral artery (MCA) peaked at 212 cm/s on day 6 and gradually decreased, whereas PSV of the left posterior cerebral artery (PCA) and left anterior cerebral artery (ACA) re-elevated to 190 cm/s on day 15. The second case involved a 53-year-old woman who developed cerebral infarction in the PCA territory 9 days after severe headache. TCCS study showed PSV elevation in the right MCA. Although TCCS seemed to normalize 7 days after admission, PSV of the left PCA, left ACA, and left MCA re-elevated at day 17. Both cases showed bimodal PSV peaks, with the posterior circulation peak preceded by the anterior circulation peak. These findings may be important in clarifying the mechanisms underlying vasoconstriction in patients with RCVS.